Primary Trans-anal Endorectal Pull Through for The Management of Hirschsprung Disease: Our Experience of 20 Cases: Primary Trans-anal Endorectal Pull Through for Hirschsprung Disease - Haider, Naveed Haider; Sulman Butt, Muhammad; Varda, Komal; Shahbaz , Ferheen; Ajaz, Maryam; Saeed, Afeefa; Saleem, Javeria (Pakistan Journal of Health Sciences, 2022)
Hirschsprung’s disease can be defined in terms of the aganglionic part of the colon and the definitive treatment is a one-stage trans-anal endorectal pull-through surgery. Objectives: To find out the efficacy and safety of this one-stage pull-through. Mostly the surgery is done in early childhood or the neonatal period, as the case is less frequently reported in older children and adolescents. Methods: A retrospective study was conducted including 16 males and 4 females. 20 cases including children of 6 months to 14 years, all were diagnosed with Hirschsprung’s disease in the study duration of two years. The diagnostic criteria of these patients included; Clinical history of delayed passage of meconium, contrast enema, and rectal biopsy. Definitive variables were; Age, sex, and length of the aganglionic part of the colon. Results: All the patients included in the study had distended abdomens and persistent constipation. All of them have an aganglionic colon, a diagnosing feature of Hirschsprung’s disease. All patients underwent the trans-anal endorectal one-stage pull-through. The average operative time recorded was 150 minutes. Post-operative complications were also recorded including anastomosis leakage (only in one case; for that a diversion colostomy was done), anastomotic stenosis or stricture (not reported in any case), enterocolitis and perineum irritation (In four cases), Transient fecal incontinence is a major complication (11 cases had transient fecal incontinence which resolved spontaneously with 1 to 2 weeks). No death had been recorded. Conclusion: For the treatment of Hirschsprung’s disease, primary trans-anal endorectal pull-through is a safe and efficient technique.